Uses of arduino and mit app inventor in digital communication: systematic review (Research, Society and Development, 2022)
In order to understand the use of Arduino and Mit App Inventor in digital communication, a survey of articles published from 2017 to 2021 were gathered by searching the Scielo, IEEE, Science Direct, Scopus and Web of Science databases using a search string in order to reduce the scope of information, resulting in 30 initial articles. From the articles obtained and with the help of the StArt software and previously defined selection criteria, the information present in the articles was extracted and separated into breakdowns representing their objectives, methodologies, and results, as well as their title and author. Only 12 papers were used in the end, becoming part of the Systematic Review and a solid base for the objective of controlling a biodiesel engine through remote communication.